Meningkatkan Pengembangan Motorik Halus Anak Melalui Finger Painting Pada Anak Usia Dini Kelompok A Di TK Al Hidayah Terpadu I Samboja - Farida Farida; Roro Dwi Rahayu (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This study aims to improve fine motor development through finger painting in group A early childhood at TK Al-Hidayah Terpadu I Samboja Kutai Kartanegara. Data collection methods used are observation, interviews, and documentation. This research is a population study where members of the population are used as research subjects. The research data obtained were then analyzed using a percentage score which later could be known about the extent of fine motor development through finger painting. In observation 1 it can be seen that 16.7% of the 30 children have progressed in finger painting activities, while 33.3% of the children are starting to develop and 50% of the children are still in the undeveloped category. And in observation 2 it can be seen that 40% of the 30 children have developed in finger painting activities, 26.7% of children are starting to develop and 33.3% of children are still categorized as not yet developing in finger painting activities.